2009
DOI: 10.1002/jbm.a.32270
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and in vivo evaluation of oligochitosans as cationic modifiers of alginate/Ca microcapsules

Abstract: The present article investigates the substitution of poly-L-lysine by two different oligochitosans as membrane-coating capsule, and its effect on different functionality parameters of cell microencapsulation. To address this issue, initially the biocompatibility of the two types of oligochitosan solutions was evaluated using erythropoietin secreting C2C12 myoblast cell line as model. In a second step, we encapsulated the cells within alginate microcapsules coated with each oligochitosan and a complete morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
(66 reference statements)
2
8
0
Order By: Relevance
“…In respect to hepatic function in T1 group, a promising result was found when evaluating safety in the use of new biomaterials, since the groups that received ZA + insertion of both scaffolds had their AST and ALT activities similar to the control. This finding corroborates the fact that the chitosan/sodium alginate/hydroxyapatite mixture is biocompatible and does not present hepatic toxicity . Elevated serum levels of AST and ALT are found in hepatic injury, signaling the rupture of hepatocytes with extravasation of transaminases to the circulation .…”
Section: Discussionsupporting
confidence: 83%
“…In respect to hepatic function in T1 group, a promising result was found when evaluating safety in the use of new biomaterials, since the groups that received ZA + insertion of both scaffolds had their AST and ALT activities similar to the control. This finding corroborates the fact that the chitosan/sodium alginate/hydroxyapatite mixture is biocompatible and does not present hepatic toxicity . Elevated serum levels of AST and ALT are found in hepatic injury, signaling the rupture of hepatocytes with extravasation of transaminases to the circulation .…”
Section: Discussionsupporting
confidence: 83%
“…This prolonged exposure of mammalian cells to the low pH results in low cell viability after coating. In addition, the swelling and breaking of alginate-chitosan-alginate (ACA) microcapsules are difficult to overcome when liquefying the alginate core using sodium citrate solution [19, 36, 37]. Moreover, long-term biocompatibility of chitosan and other polycations in vivo needs to be further evaluated rigorously.…”
Section: Materials and Methods For Microencapsulation Of Mammalianmentioning
confidence: 99%
“…106,107 Recently, modified oligochitosans (quaternary ammonium derivative oligochitosans) have been proposed as an interesting possible alternative to the currently PLL. 108 Results obtained both in vitro and in vivo demonstrated that modified oligochitosans are biocompatible and allow the elaboration of microcapsules mechanically stable at physiological pH.…”
Section: Cross-linking Ionsmentioning
confidence: 98%